Aegle marvels (L.) Correa Leaf Essential Oil and Its Phytoconstituents as an Anticancer and Anti-Streptococcus mutans Agent - Alhussain H. Aodah; Mohamed F. Balaha; Talha Jawaid; Mohammed Moizuddin Khan; Mohammad Javed Ansari; Aftab Alam (MDPI AG, 2023)
Aegle mamelons (A. marmelos) or Indian Bael leaves possess anti-cancerous and antibacterial properties and are used in the traditional medicine system for the treatment of oral infections. In the present study, the essential oil of the leaves of A. marmelos was explored for its anticancer, antioxidant, and anti-cariogenic properties. The hydro-distilled oil of A. marmelos leaves was analyzed using gas chromatography coupled with mass spectrometry (GC-MS). Monoterpene limonene (63.71%) was found to have the highest percentage after trans-2-Hydroxy-1,8-cineole and p-Menth-2,8-dien-1-ol. The MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay was used to investigate the anticancer activity of the extracted oil against human oral epidermal carcinoma (KB), and the results showed significantly higher (**** p < 0.0001) anticancer activity (45.89%) in the doxorubicin (47.87%) when compared to the normal control. The antioxidant activity of the essential oil was evaluated using methods of DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)). The results showed a significant (*** p < 0.001) percentage of inhibition of DPPH-induced free radical (70.02 ± 1.6%) and ABTS-induced free radical (70.7 ± 1.32%) at 100 µg/mL with IC50, 72.51 and 67.33 µg/mL, respectively, comparatively lower than standard compound ascorbic acid. The results of the molecular docking study of the significant compound limonene with the receptors tyrosinase and tyrosine kinase 2 supported the in vitro antioxidant potential. The anti-cariogenic activity was evaluated against Streptococcus mutans (S. mutans). Results showed a significant minimum inhibitor concentration of 0.25 mg/mL and the killing time was achieved at 3 to 6 h. The molecular-docking study showed that limonene inhibits the surface receptors of the S. mutans c-terminal domain and CviR protein. The study found that A. marmelos leaves have potential anti-carcinoma, antioxidant, and anti-cariogenic effects on human oral epidermal health, making them a valuable natural therapeutic agent for managing oral cancer and infections.